Stategi Guru Pendidikan Agama Islam dalam Membentuk Karakter Jujur pada Peserta Didik Kelas VIII A - Imam Sujai (Universitas Islam Tribakti Lirboyo Kediri, 2025)
Currently, it is very difficult to find honest characters inherent in students. There are many cases of cheating in carrying out exams. It takes the right handler to form an honest character in students. Therefore, the right strategy is needed to be able to realize students with honest characters. This research method uses a qualitative method and by means of interviews, observations, and documentation as data collection techniques. The results of this study show the strategy of Islamic religious education teachers in instilling honest characters in class VIII A students at SMP Negeri 1 Semen is by making it a habit, providing examples, using storytelling methods and giving punishments or rewards. Supporting factors for Islamic religious education teachers in instilling honest characters in class VIII A students at SMP Negeri 1 Semen are cooperation between all teachers, school facilities and extracurricular activities. While the inhibiting factors include lack of motivation and awareness of students, lack of parental guidance and the influence of social media. Keywords: Strategy, Islamic Religious Education Teachers, Character, Honest